Recurrence analysis of time series generated by 3D autonomous quadratic dynamical system depending on parameters - V. Ye. Belozyorov; V. G. Zaytsev (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Modelûvannâ, 2016)
For the wide class of 3D autonomous quadratic dynamical systems depending on parameters the sucient conditions of boundedness of solutions of any system from this class are found. A connection between change of one of the parameters and a recurrence plot structure, which was built on the time series for any system of this class, is determined. Due to this connection it is possible to nd bifurcation values of the parameter of any system from the considered class only on its time series without knowledge of dierential equations of this system. Examples are given.